1967
DOI: 10.1002/pol.1967.150050104
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation between catalysts, alcohols, and isocyanates in the preparation of urethanes

Abstract: SynopsisThe mechanism of the catalyzed reaction between alcohols and isocyanates was investigated by means of NMR, infrared, and ultraviolet spectroscopy. The shift of the --OH proton resonance in the N M R spectra indicated the existence of a 1: 1 complex in the system dibutyltin dilaurate (DBTDLp1-methoxy-Zpropanol. Complex formation was also observed when lead naphthenate or triethylamine (TEA) were substituted for the DBTDL. Mixtures of the DBTDLTEA catalysts caused a shift of the -OH proton resonance grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…In order to describe our experimental data we considered valid, at first approximation, the mechanism proposed by Frish et al 39,40 and Entelis 41,42 :…”
Section: Resultsmentioning
confidence: 99%
“…In order to describe our experimental data we considered valid, at first approximation, the mechanism proposed by Frish et al 39,40 and Entelis 41,42 :…”
Section: Resultsmentioning
confidence: 99%
“…Although polyurethane reactions have been subjected to a great number of studies that have suggested various mechanisms for urethane or urea formation, very little attention has been paid to the mechanistic aspects of the autocatalytic effects themselves. 7 In particular, no previously proposed mechanism provides a satisfactory interpretation of the experimental results mentioned previously. In this article, a kinetic study, using quantitative Fourier transform infrared (FTIR) spectroscopy, is performed to gain insight into the mechanism of the autocatalytic effect of the reactions of urethane and urea in the bulk state.…”
Section: Introductionmentioning
confidence: 91%
“…For four series of reactions with different reagent concentrations, we have log R 04 ϭ log k ϩ nЈ log͓NCO͔ 04 ϩ hЈ log͓OH͔ 04 ϩ d log͓DBTDL͔ 04 (19) log R 05 ϭ log k ϩ nЈ log͓NCO͔ 05 ϩ hЈ log͓OH͔ 05 ϩ d log͓DBTDL͔ 05 (20) log R 06 ϭ log k ϩ nЈ log͓NCO͔ 06 ϩ hЈ log͓OH͔ 06 ϩ d log͓DBTDL͔ 06 (21) log R 07 ϭ log k ϩ nЈ log͓NCO͔ 07 ϩ hЈ log͓OH͔ 07 ϩ d log͓DBTDL͔ 07 (22) In this experiment, four series of reaction conditions, as shown in (k ϭ 1, 2) are known, after determining the initial reaction rates R 01 , R 02 , and R 03 , and R 04 , reaction orders h', n', and d can be computed. Following the same method as that developed for the study of a noncatalyzed system, the NCO concentration changes as a function of reaction time for each reaction system was measured, and [NCO] as a function of time (Figure 4) was determined.…”
mentioning
confidence: 99%